Antioxidant and alpha-glucosidase inhibitory activities of flavonoids isolated from fermented leaves of Camellia chrysantha (Hu) Tuyama - Tran Thi Nhu Hang; Tran Thi Tuyen; Pham Bach Cao; Hoang Kim Chi; Nguyen Tien Quan; Trinh Anh Vien; Nguyen Van Thi Hong (Türk Biyokimya Dergisi)
Microbial fermentation has long been known as a method for processing teas to raise products with novel biological activities. Our study aimed to chemically characterize flavonoid components in fungal mediated biotransformed Camellia chrysantha (Hu) Tuyama leaves.